Contributions of in-vitro biology to cassava improvement - Thro, Ann Marie; Roca, W.; Iglesias, C.A.; Henry, Guy; Ng, S.Y.C. (1998)
Cassava (Manihot esculenta Crantz) is a tough and productive survival crop of smallholder farmers in the tropics. It is often grown where other crops fail. Research can make important contribution to food security and economic development in cassava-growing areas. This can be enhanced through in-vitro propagation methods for this crop, due to its slow vegetative propagation. For useful biotechnology innovations to reach smallholder cassava farmers, a combined effort is essential, with participation of farmers and other partners in research and development. The Cassava Biotechnology Network combines forces to mobilise biotechnology as a tool for enhancing cassava's value for food security and as a means of access to economic development. In-vitro biology methods are essential to safe and efficient conservation and exchange of cassava diversity. Transgenic methods, now nearing the stage of first field trials, may offer a means of adding disease resistance or enhanced crop quality characteristics to existing preferred varieties.